Kartagener syndrome : case report and literature review (2017)
Kartagener syndrome us a rare autosomal recessive disease (one in every 32,000 births), characterized by a triad of bronchiectasis, chronic sinusitis and situs inversus. We present the case of a 24-year-old male with this disease and we review the pathoph